Reliability of WBG Transistors - Horký, Jan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
Silicon Carbide (SiC) and Gallium Nitride (GaN) transistors have the potential to revolutionize power electronics industry. They have better resistance, size, and efficiency than current Silicon (Si) transistors. On the other hand, as Silicon FET has been used for several decades, its reliability and robustness has been well known and documented. The aim of this paper is to present a review of reliability and radiation issues of GaN and SiC transistors in order to mitigate potential issues in future designs.
Keywords: Bandgap; Si; GaN; SiC; Transistor; HEMT; Radiation; Reliability; Robustness